2010
DOI: 10.1158/1055-9965.epi-09-1174
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Superoxide Dismutase Polymorphism and Risk of Gastric Lesions, and Its Effects on Chemoprevention in a Chinese Population

Abstract: Background: Manganese superoxide dismutase is the primary antioxidant enzyme in the mitochondria and is involved in carcinogenesis. To investigate the association between MnSOD Val 16 Ala polymorphism

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…On the basis of our cross‐sectional study at baseline, we found that the total score of H. pylori antibodies was markedly increased in subjects with CAG and IM, particularly for CAG, supporting our previous findings that H. pylori may play an important role in the inflammation process and early stage of gastric lesions . Interestingly, no significant association with DYS was found, consistent with the hypothesis and our previous studies that with the progression of gastric lesions toward GC, H. pylori can be lost in the stomach mucosa owing to the changed internal environment, associated with declining antibody positivity (86.8% for CAG versus 78.0% for DYS or 83.5% for CAG versus 75.2% for DYS) and titers. Indeed, when comparing baseline serum IgG titer by ELISA between CAG and DYS groups of cohort 1, we found that the mean IgG titer was lower in the DYS group than in the CAG group (2.79 ± 1.64 for CAG versus 2.43 ± 1.80 for DYS, p = 0.0128).…”
Section: Discussionsupporting
confidence: 90%
“…On the basis of our cross‐sectional study at baseline, we found that the total score of H. pylori antibodies was markedly increased in subjects with CAG and IM, particularly for CAG, supporting our previous findings that H. pylori may play an important role in the inflammation process and early stage of gastric lesions . Interestingly, no significant association with DYS was found, consistent with the hypothesis and our previous studies that with the progression of gastric lesions toward GC, H. pylori can be lost in the stomach mucosa owing to the changed internal environment, associated with declining antibody positivity (86.8% for CAG versus 78.0% for DYS or 83.5% for CAG versus 75.2% for DYS) and titers. Indeed, when comparing baseline serum IgG titer by ELISA between CAG and DYS groups of cohort 1, we found that the mean IgG titer was lower in the DYS group than in the CAG group (2.79 ± 1.64 for CAG versus 2.43 ± 1.80 for DYS, p = 0.0128).…”
Section: Discussionsupporting
confidence: 90%
“…Catalase has been reported to be responsible for the detoxification of H 2 O 2 , which is an effective inhibitor of SOD. Other researchers reported the same results [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 77%
“…The frequency distributions of C and T alleles were found to be respec- has the similar CC genotype frequency as seen in AfricanAmerican [35], Finn [36], and Italian populations [37]. We detected considerably lower CC genotype frequency than those found in Korean [38], Japan [39], Chinese [40] and Taiwan [41] populations and higher frequencies than those found in American [23], Polish [42], Danish [43], German [44] and Russian [45] populations. Eventually, CC genotype frequency in populations of the eastern countries, were lower (between 0-17%) found than the western countries (between 42-67%) ( Table 4).…”
Section: Resultssupporting
confidence: 75%